Pendampingan Latihan Seni Menulis Kaligrafi bagi Santri Pondok Pesantren Baqiyatussa'adiyah di Sanggar Assifa Kabupaten Indragiri Hilir - Muhammadiyah Muhammadiyah; Zulkifli Zulkifli; Zulkarnainsyah Zulkarnainsyah; Rita Kencana (STAI Auliaurrasyidin Tembilahan, 2022)
Assistance in the art of writing calligraphy held by the Assifa studio for students at the Baqiyqtussa'adiya Islamic boarding school. Calligraphy is a writing art that regulates the forms of letters, their locations, and ways of assembling them into an organized writing and requires creativity and appreciation in writing. Assistance is carried out aiming to train the art of calligraphy writing. This mentoring activity begins by providing material about the types of calligraphy khat and how the characters of each of these khat are. Furthermore, the students were introduced to the basic techniques of calligraphy using kalam. The method was carried out in the assistance of calligraphy writing exercises directly to the students of the Baqiyqtussa'adiyah Islamic boarding school. This activity is carried out during this training assistance activity carried out for 1 month, namely August 1 2022 to August 31 2022, every Wednesday and Saturday at 13.30 to 16.30 WIB. Individual training participants are able to write the art of calligraphy which has been taught in the assifa studio of the Auliaurrasyidin Tembilahan Islamic High School.